Excitation-Contraction Coupling and Minor Triadic Proteins in Low-Frequency Fatigue - Balog, Edward M. (2010)
Low-frequency fatigue (LFF) is characterized by a proportionally greater loss of force at low compared to high activation frequencies and a prolonged recovery. Recent work suggests a calcium-induced uncoupling of excitation-contraction coupling underlies LFF. Here newly characterized triadic proteins are described and possible mechanisms by which they may contribute to LFF are suggested.